The Utilization of Communicative Translation Principles in Translating The Gojek Application Into English - Dharma, I Nyoman Surya; Indrawati, Ni Luh Ketut Mas; Aryani, I Gusti Agung Istri (International Journal of Linguistics and Discourse Analytics, 2025)
In the digital era, applications have become essential tools for daily activities, particularly in Indonesia. As local apps like Gojek expand into international markets, translation is not only a matter of transferring language but also of ensuring that messages are effectively communicated to target users. This study analyzed the application of Newmark’s communicative translation principles in the English version of the Gojek app. Using a descriptive qualitative approach, the research examined data from Gojek version 5.18.0, collected through screenshots of the Indonesian and English user interfaces. The analysis focused on three principles: naturalness, equivalent effect, and information accuracy. Findings from seven data samples indicated that these principles were consistently applied. Naturalness was reflected in language that read smoothly and was easily understood. The equivalent effect was maintained through the preservation of vocative and informative functions. Information accuracy, particularly in technical terminology, enhanced user comprehension. Overall, applying communicative translation principles improves user experience and supports global market accessibility while offering guidance for translators and UX writers.